Covid-19 Morbidity amongst Covishield Vaccinated Vs Non-Vaccinated: A Comparative Study - Vikas Yadav; Poninder Kumar; Arvind Kushal; Renu Yadav; Priya Anjali (Medsci Publications, 2022)
Introduction: Covid-19 pandemic is further spreading its leg in India. Indigenous Covishield vaccination drive was started to protect people from the disease. Objective: This observational cross sectional study was conducted to assess the morbidity and mortality pattern amongst Covishield vaccinated people Vs non-vaccinated patients of covid19. Methodology: This observation study was conducted in a dedicated covid-19 hospital. All RTPCR covid-19 patients were included. The data on vaccination against covid-19 amongst the patients was obtained, and analysed using statistical software. Results: The study population comprised of 155 cases of confirmed covid-19 patients of which 24 (15.48%) were fully vaccinated, however 41 (26.45%) and 90 (58.06%) were partially and non-vaccinated respectively. Fully vaccinated people were protected from development of severe form of disease (X2=9.57, d.f=2, p=0.0083). Mortality was significantly less amongst vaccinated group (X2=4.83, d.f=1, p= 0.028). Conclusion: Patients who are completely vaccinated with Covishield vaccine are protected from development of severe form of diseases and deaths and hence mass vaccination of Indian population to overcome the pandemic is required at the earliest.